Pengaruh Teknik Token Ekonomi Terhadap Perilaku Belajar Siswa untuk Mengurangi Perilaku Off Task - Siti Meyzrah Zuhara; Rahmawati, Rahmawati; Handoyo, Alfandy Warih (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
ABSTRACT The purpose of the study was to determine the effect of the token economy technique on students' off task behavior. The type of research used is experimental research with single subject research with 5 students who have off task behavior, lack of motivation to learn in doing assignments, understand the material presented by the teacher, lack of enthusiasm to take part in online learning. The data collection method used an off task behavior questionnaire consisting of 43 statement items with a reliability value (rcount) of 0.615. The results obtained by the subject are seen from the change in the level of data in subject 1 of the analysis between conditions in the intervention phase (B) to baseline-1 (A), increasing by (41) points due to the treatment. While in the baseline-2 phase (A2) to intervention (B) there was an increase of (-22) points. In subject 2, the analysis between conditions in the intervention phase (B) to baseline-1 (A), increased by (33) points due to the treatment. Meanwhile, in the baseline-2 (A2) to intervention (B) phase, there was an increase of (-22) points and subjects 3 to 5 were analyzed between conditions in the intervention phase (B) to baseline-1 (A), increasing by (33) points due to the treatment. Meanwhile, in the baseline-2 phase (A2) to intervention (B) there was an increase of (-20) points. Although the baseline-2 phase was obtained higher than the baselineÂ¬-1 phase (A1). In addition, data overlap in the intervention phase (B) to baseline-1 (A1) and the baseline-2 (A2) to intervention (B) phase has an overlap percentage of 0%, so it can be concluded that the Economic Token Technique can reduce the off task behavior of class XII students. IPA SMAN 10 Pandeglang. Keywords: Token Economy Technique, Off Task Behavior